Assessment of Ornamental Plant Ruellia simplex and Bio-Adsorbent for Removal of Amoxicillin and Ciprofloxacin ? A Preliminary Test for Constructed Wetlands - Alsalihy S.T.H.; Hayder G.; Ahmed A.N.; M-Ridha M.J.; Ewadh H.M. (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2025)
One of the procedures that helps remove pharmaceuticals (Phs) from wastewater in Constructed Wetlands (CWs) is phytoremediation. Using Ruellia simplex, the main emphasis of this study is on the function of plants and substrates in the removal mechanism independently from aqueous solution. Even in an aqueous solution containing high concentrations of antibiotics, the plant could thrive, and lighting further promoted growth. For the removal of amoxicillin (AMX) and ciprofloxacin (CIP) at a concentration of 25 mg/L, six reactors are used: hydroponic planted reactors, sand rectors, chicken manure ? wood shavings (CM-WS) rectors, rhizobacterial-inoculated unplanted reactors, unplanted control reactors, and unplanted dark control reactors to study the roles of phytoremediation, adsorption, biodegradation, photodegradation and hydrolysis process in reduction of AMX and CIP. Additionally, the plant?s weight is determined for each sample collected and compared to the initial weight of the experiment to monitor plant growth. The possible fates of AMX and CIP were explored using hydroponic tests, whereby 43%, 26% and 19%, respectively, of the total removal of AMX had been accounted for by plant uptake, adsorption by CM-WS and biodegradation after 21 days of exposure, also these process contributed well in CIP removal, where the proportions were 39%, 32% and 18%, respectively of the total CIP reduction at the same intervals. ? (2024), (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE)). All rights reserved.